2017
DOI: 10.1038/nm.4283
|View full text |Cite
|
Sign up to set email alerts
|

The creatine kinase pathway is a metabolic vulnerability in EVI1-positive acute myeloid leukemia

Abstract: Expression of the EVI1 proto-oncogene is deregulated by chromosomal translocations in some cases of acute myeloid leukemia (AML) and is associated with poor clinical outcome. Here, through transcriptomic and metabolomic profiling of hematopoietic cells, we reveal that EVI1 overexpression alters cellular metabolism. A pooled shRNA screen identified the ATP-buffering, mitochondrial creatine kinase CKMT1 as a metabolic dependency in EVI1-positive AML. EVI1 promotes CKMT1 expression by repressing the myeloid diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
101
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 58 publications
1
101
0
1
Order By: Relevance
“…[46,47] SG animals also had an upregulation in MECOM regulated pathways, which are associated with increased purine and pyrimidine metabolism, amino acid metabolism, pentose phosphate pathway reliance, and glycolysis. [48]. Elevations in PPARg, SMRT, and NCOR which all interact to control downstream adipocyte fate and function, glucose handling, insulin sensitivity, mitochondrial oxidative capacity, and thermogenesis, were also found.…”
Section: Discussionmentioning
confidence: 94%
“…[46,47] SG animals also had an upregulation in MECOM regulated pathways, which are associated with increased purine and pyrimidine metabolism, amino acid metabolism, pentose phosphate pathway reliance, and glycolysis. [48]. Elevations in PPARg, SMRT, and NCOR which all interact to control downstream adipocyte fate and function, glucose handling, insulin sensitivity, mitochondrial oxidative capacity, and thermogenesis, were also found.…”
Section: Discussionmentioning
confidence: 94%
“…As a result, they demonstrated that SCC instead of AC has an amplified region of gene in 3q26.2–q29, where the EVI1 gene is located 10. Many previous studies have proved the oncogenic role of EVI1 in tumors, especially tumors of hematopoietic system 17. More and more emerging evidence has indicated the oncogenic role of EVI1 in solid tumors, including prostate cancer, ovarian cancer, glioblastoma, hepatocellular carcinoma, and so on 7,9,18.…”
Section: Discussionmentioning
confidence: 99%
“…KCRB depletion/inhibition in combination with chemotherapeutic agents showed synergistic effects in cancer therapy (47). Cr kinase metabolic inhibition by cc was shown to decrease cell viability, promote cell-cycle arrest, and apoptosis in EVI1 (48). Inhibition of the colon cancer cell line KCRB by preincubation with cc reduced liver metastasis formation and depleted PCr (49) and recently, mice inoculated with colorectal cancer cells and treated with cc showed a significant reduction in metastatic colonization (19).…”
Section: Discussionmentioning
confidence: 99%